Analysis of Local Capacity in Overcoming Program Fragmentation of the Uninhabitable House Program in Karawang Regency: Analisis Kapasitas Lokal dalam Mengatasi Fragmentasi Program Rumah Tidak Layak Huni di Kabupaten Karawang - Eka Ashari; Hanny Purnamasari (Universitas Indo Global Mandiri, 2026)
Purpose : This research aims to analyze the implementation of the Uninhabitable House (Rutilahu/RTLH) policy in Karawang Regency using Merilee S. Grindle’s policy implementation framework, with a focus on the role of Local Capacity in responding to program fragmentation at the multi-level governance scale. Design/methodology/approach : This study employed a descriptive qualitative method to examine the dynamics of public policy implementation. Primary data were collected through observation, in-depth interviews with village officials, and documentation. Data analysis was conducted through reduction, presentation, and conclusion drawing, guided by Grindle’s implementation theory. Findings : The implementation of the RTLH policy has generally improved housing quality and community welfare. However, program fragmentation between district and provincial schemes, such as the Aladin Program, creates disparities in resource distribution and access for the extremely poor. The capacity and commitment of village governments emerged as a key determinant of success, demonstrated by consistent data input of 78 RTLH units into the SIIMAH system and adaptive administrative measures, including the issuance of domicile certificates (SKD) to address land legality constraints. Practical Implication : Regulatory synchronization and institutional role reformulation among central, provincial, and district governments are necessary to reduce program fragmentation. Incentives for active villages and a more inclusive Aladin Program design are recommended. Originality/value : This study extends Grindle’s implementation theory by emphasizing the adaptive capacity of local implementers in overcoming structural and resource limitations.